Archival Readiness: Archive Making in an Emergency Shelter - Turner, Alison (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
This article explores the challenges of engaging historically excluded communities with archives and archival discourse, focusing on people and communities experiencing homelessness. Positioning the phrase literal homelessness, which is used in the United States to determine eligibility for an annual census of people experiencing homelessness, as representative of ongoing exclusive and non-collaborative forms of recordkeeping, the author proposes a concept that she calls archival readiness to move toward archive making, rather than archive taking, with historically excluded communities. Using her experiences as a part-time staff member in a temporary emergency shelter that was established during the COVID-19 pandemic, she shows how archival readiness, based on ongoing relationships among archivists, researchers, community organizations, and individuals, would increase the likelihood that shelter guests would participate in archiving. Exploring how homelessness creates challenges for the development of inclusive institutional and community-archiving praxes, she argues that while archival readiness would not solve each of these challenges, it could enable historically excluded communities to participate in generating other approaches. The author enacts archival readiness by sharing three records from the shelter and her interpretations of them, introducing forms of information about shelter living that is not collected in official data that tracks “literal homelessness.”